Two pairs of alkaloid enantiomers from Ganoderma luteomarginatum. (October 2019) - Li, Xiao-Cui; Liu, Fei; Su, Hai-Guo; Guo, Li; Zhou, Qin-Mei; Huang, Yuan-Jin; Peng, Cheng; Xiong, Liang
Abstract: A pair of new alkaloid enantiomers [(+)- and (−)-1 ] as well as a pair of known enantiomeric analogues [(+)- and (−)-2 ] were isolated from the fruiting bodies of Ganoderma luteomarginatum . Their planar structures were determined by extensive spectroscopic analyses. The absolute configurations were established by comparison of the experimental and calculated electronic circular dichroism (ECD) or comparison of the experimental and reported specific optical rotation ([α]D ). These rare Ganoderma alkaloids have a phenyl-substituted 6, 7-dihydro-5 H -cyclopenta[ c ]pyridine skeleton that has only been reported from the genus Ganoderma . The (+)- and (−)-1 were new Ganoderma alkaloids, while (+)- and (−)-2 were isolated from G. luteomarginatum for the first time. Thus, these four isolates could be tentatively determined as chemotaxonomic constituents of G. luteomarginatum . Graphical abstract: Image 1 Highlights: Two pairs of unusual alkaloid enantiomers are first reported from Ganoderma luteomarginatum. All compounds possessed a rare phenyl-substituted cyclopenta[ c ]pyridine skeleton. Phenyl-substituted cyclopenta[ c ]pyridine alkaloids have only been reported in Ganoderma. This study revealed the chemtaxonomic significance of these uncommon alkaloids in Ganoderma.